2021
DOI: 10.1021/acsami.1c02119
|View full text |Cite
|
Sign up to set email alerts
|

Dual Resistance and Impedance Investigation: Ultrasensitive and Stable Humidity Detection of Molybdenum Disulfide Nanosheet-Polyethylene Oxide Hybrids

Abstract: There is an imperative demand for real-time relative humidity (RH) discrimination with excellent sensitivity and robust operation stability over a broad RH range at room temperature (22 °C). Of diverse two-dimensional (2D) materials, p-type molybdenum disulfide (MoS2) as a typical gas-sensing candidate has been rarely harnessed for humidity detection due to tiny response and undesirable stability induced by the conversion from electron to proton conduction with increasing RH. To overcome these issues, MoS2-pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 56 publications
2
33
0
Order By: Relevance
“…Liquid-phase exfoliations of bulk MoS 2 via a facile ultrasonic treatment in organic solvents, e.g. ethanol, [19][20] 2-propanol, 21 N-methyl-2pyrrolidone, 22 acetone and alcohols (ethanol, methanol and isopropanol), 23 or in aqueous solution with auxiliary reagents such as thiolated surfactants, 24 polystyrene-polyacrylamide, 25 bovine serum albumin, 26 poly(3,4-ethylenedioxythiophene): poly-(styrenesulfonate), 27 Nafion, 28 polymeric ionic liquid, 29 have been successfully developed and widely applied in the field of catalysis, organic solar cells, antibacterial, conductive films, et al Nevertheless, organic solvents, surfactants, polymers are mostly toxic, which will cause adverse effects on biological applications. Therefore, a facile method for the exfoliation and functionalization of MoS 2 nanosheets with a green and cost-effective auxiliary reagent to reinforce their biocompatibility and functionality for biological application is highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid-phase exfoliations of bulk MoS 2 via a facile ultrasonic treatment in organic solvents, e.g. ethanol, [19][20] 2-propanol, 21 N-methyl-2pyrrolidone, 22 acetone and alcohols (ethanol, methanol and isopropanol), 23 or in aqueous solution with auxiliary reagents such as thiolated surfactants, 24 polystyrene-polyacrylamide, 25 bovine serum albumin, 26 poly(3,4-ethylenedioxythiophene): poly-(styrenesulfonate), 27 Nafion, 28 polymeric ionic liquid, 29 have been successfully developed and widely applied in the field of catalysis, organic solar cells, antibacterial, conductive films, et al Nevertheless, organic solvents, surfactants, polymers are mostly toxic, which will cause adverse effects on biological applications. Therefore, a facile method for the exfoliation and functionalization of MoS 2 nanosheets with a green and cost-effective auxiliary reagent to reinforce their biocompatibility and functionality for biological application is highly desired.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods, including gas chromatography ( Kay et al, 2021 ) and electrochemical methods ( Marecek and Samec 2020 ), have also been reported. These methods, which rely either on the detection of water directly or on the detection of signal changes corresponding to other molecules that interact with water, generally lead to extremely high sensitivity and selectivity ( Wang et al, 2021 ). Nonetheless, ongoing challenges in using such methods include the need for costly and non-portable laboratory-grade instruments to monitor such spectral changes, as well as the fact that many of these methods are not reversible.…”
Section: Introductionmentioning
confidence: 99%
“…Some others include gas [6] employing titanium dioxide (TiO 2 ) nanoparticles decorated BP nanosheets as the sensing layer to detect ammonia [7]. Humidity [8] and moisture sensors that are also able to detect exhaled gas and distance variation of moisture emitting objects [9] are also in use. In our daily life, wearable sensors have become a part of health monitoring [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous sensors based on various principles and substrates are available for the detection and monitoring of humidity and moisture [9,[24][25][26][27]. These are capacitive, resistive (inductive) LC resonators or optical sensors.…”
Section: Introductionmentioning
confidence: 99%